Anti Covid-19 Drugs Suggested by Computational Methods: A Review - B. Reshika; Samiksha Shivaji Bhor (International Journal of Cell Biology and Cellular Functions, 2023)
Background and aims: Long COVID refers to the persistence of illness in individuals who have survived from COVID-19 infection. This article reviews long covid and the use of in silico techniques in drug development for COVID-19. Results: Many COVID-19 survivors have long COVID, which has become a burden in daily life. Various attempts have been undertaken to relieve symptoms and manage it, but there is no cure as of yet. Healthy lifestyle practices and periodic health assessment could be of some help. Many plant phytochemicals, synthetic medicines, and other compounds show tremendous potential in computational analysis and should be studied further in the laboratory employing in vivo and in vitro approaches to understand their biochemistry in the human body. Conclusions: This review will assist investigators in analyzing long COVID and further exploring the given compounds in order to find a cure for COVID-19.
Keywords: Drug discovery; Long COVID; Pandemic; Sars-CoV-2; molecular docking